2022
DOI: 10.1038/s41440-022-01008-w
|View full text |Cite
|
Sign up to set email alerts
|

The renoprotective effect of esaxerenone independent of blood pressure lowering: a post hoc mediation analysis of the ESAX-DN trial

Abstract: Angiotensin-converting enzyme (ACE) inhibitors or angiotensin II receptor blockers (ARBs) are recommended as first-line drugs for hypertension with diabetic nephropathy owing to their renoprotective effect; however, their effect beyond lowering blood pressure (BP) has not been confirmed. Recent studies have shown that aldosterone plays a key role in causing renal injury; therefore, it is likely that mineralocorticoid receptor (MR) blockers inhibit aldosterone-induced renal damage in different ways from ACE inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Because esaxerenone continuously reduces UACR up to 6 months after administration, followed by a steady state [ 17 ], further UACR reduction can be expected with long-term administration. Although part of this UACR-lowering effect is due to the reduction in circulating and renal blood flow by lowering BP [ 19 ], recent statistical medication analysis has shown that direct MR inhibition, independent of the antihypertensive effect, reduces UACR [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because esaxerenone continuously reduces UACR up to 6 months after administration, followed by a steady state [ 17 ], further UACR reduction can be expected with long-term administration. Although part of this UACR-lowering effect is due to the reduction in circulating and renal blood flow by lowering BP [ 19 ], recent statistical medication analysis has shown that direct MR inhibition, independent of the antihypertensive effect, reduces UACR [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study will also examine the UACR‐lowering effect as well as safety, including effects on glucose, lipid, and UA metabolism. Esaxerenone and thiazide diuretics have a similar mechanism for UACR‐lowering effects, whereby circulating and renal blood flow are reduced by lowering BP; however, esaxerenone is suggested to have another mechanism that involves direct inhibitory action against mineralocorticoid receptors in the kidney 40 . Therefore, a comparison of the UACR‐lowering effect may also provide insight into this different mechanism of UACR reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In the esaxerenone group, there was a significant reduction in blood pressure from baseline (−10/−5 mmHg) [163]. A post-hoc analysis of the study indicated that around 10% of the UACR-lowering effect of esaxerenone could be mediated by the reduction in systolic blood pressure [164].…”
Section: Esaxerenonementioning
confidence: 92%